2003 Handbook of Employment Regulations Affecting Florida Farm Employers and Workers: Migrant Farm Labor Camps [Federal] - Leo C. Polopolus; Michael T. Olexa; Fritz Roka; Carol Fountain (EDIS)
The purpose of migrant farm labor camp regulations is to provide federal standards for employer or farm labor contractor-provided housing for migrant farmworkers. This is EDIS document FE404, a publication of the Department of Food and Resource Economics, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida, Gainesville, FL. Published July 2003. This information is included in Circular 1200, Handbook of Employment Regulations Affecting Florida Farm Employers and Workers.